Interaction among cultural factors in microtuberization of white yam (Dioscorea rotundata) - Balogun, M.; Fawole, I.; Ng, S.Y.C.; Ng, N.Q.; Shiwachi, H.; Kikuno, H. (Wiley, 2006)
Single node cuttings from pathogen-tested in vitro plantlets of white guinea yam (D. rotundata), cultivar TDr 93–23, were cultured in tuberization and half- and full-strength Murashige and Skoog media with 5% or 8% sucrose, with or without agar, in light or darkness and at 25 or 18°C. Microtuberization is influenced by interactions among the factors, but 25°C and daylight are critical.